2006
DOI: 10.1007/s00127-006-0050-6
|View full text |Cite
|
Sign up to set email alerts
|

Training patients with schizophrenia with the community re-entry module

Abstract: The study supports the feasibility and effectiveness of the Chinese version of the CRM as an effective psychosocial intervention for Chinese patients with schizophrenia to improve psychopathology, social functioning and relapse and re-hospitalization rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 14 publications
2
37
0
1
Order By: Relevance
“…In total, 13 data sets compared a group psychotherapeutic treatment to an active sham group [37,39,41,42,43,44,45,46,47,48,49,50,51], and 19 data sets compared a group psychotherapeutic treatment to TAU [7,12,13,34,40,41,52,53,54,55,56,57,58,59,60,61,62,63]. Thirty-one percent of the interventions were cognitive-behavioural approaches (including cognitive-behavioural social skills training and compensatory cognitive training), 19% came under the umbrella term ‘non-verbal arts therapies' (including music therapy, body-oriented psychotherapy and art therapy), and the remaining 50% included a range of therapeutic orientations such as cognitive remediation therapy, psycho-education and integrated approaches.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 13 data sets compared a group psychotherapeutic treatment to an active sham group [37,39,41,42,43,44,45,46,47,48,49,50,51], and 19 data sets compared a group psychotherapeutic treatment to TAU [7,12,13,34,40,41,52,53,54,55,56,57,58,59,60,61,62,63]. Thirty-one percent of the interventions were cognitive-behavioural approaches (including cognitive-behavioural social skills training and compensatory cognitive training), 19% came under the umbrella term ‘non-verbal arts therapies' (including music therapy, body-oriented psychotherapy and art therapy), and the remaining 50% included a range of therapeutic orientations such as cognitive remediation therapy, psycho-education and integrated approaches.…”
Section: Resultsmentioning
confidence: 99%
“…The objectives of this study were (1) to measure and compare SQOL in Chinese schizophrenia patients between HK and Beijing (BJ) and (2) to explore the association of QOL with socio-demographic and clinical factors in the two sites.…”
mentioning
confidence: 99%
“…The authors found long-term SST had modest positive effects on functioning over a control group supportive therapy program, however clinicians were not blind to treatment group, thus findings should be viewed with caution [63]. A study conducted in Beijing, China found social functioning, as assessed by the Chinese version of the Social Disability Screening Schedule, improved significantly for patients who received 8 weeks of SST based on the community re-entry module, in comparison to those who received supportive counselling [62]. In a more recent study Cirici et al [58] used the Social Behaviour Assessment Schedule [66], an informant interview-based measure of social functioning, as well as a self-report measures to test the effects of 20 weeks SST in schizophrenia outpatients.…”
Section: Historical Approaches To Treatment Of Social Disabilitymentioning
confidence: 99%